Persepsi dan Sikap Mahasiswa Terhadap Korupsi pada Peserta Mata Kuliah Pendidikan Anti Korupsi di Rombel Ilmu Politik FISIP UNNES (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the perceptions and attitudes of students participating in the Anti-Corruption Education course in the Political Science class of FISIP UNNES toward corruption. The research employed a qualitative descriptive approach. The subjects of this study were students enrolled in the Anti-Corruption Education course in one Political Science learning group at FISIP UNNES. Data were collected through open-ended questionnaires and analyzed using thematic analysis involving data reduction, theme categorization, data presentation, and conclusion drawing. The results showed that students perceive corruption not only as an abuse of power and a violation of law, but also as a moral and social problem that damages public trust and hinders development. Students demonstrated anti-corruption attitudes through rejection of corruptive behavior, including academic dishonesty such as cheating, plagiarism, and attendance fraud. Anti-Corruption Education was considered effective in developing integrity, moral awareness, critical thinking, and personal responsibility among students. In addition, contextual learning methods such as discussions and case studies were perceived as more effective in strengthening students’ anti-corruption awareness and attitudes. This study indicates that Anti-Corruption Education plays an important role in building character and fostering an anti-corruption culture in higher education.